Explaining How Survivors Respond to Downsizing: The Roles of Trust, Empowerment, Justice, and Work Redesign - Mishra, Aneil K.; Spreitzer, Gretchen M. (Academy of Management Review, 1998)
Aneil K. Mishra, Gretchen M. Spreitzer, Explaining How Survivors Respond to Downsizing: The Roles of Trust, Empowerment, Justice, and Work Redesign, The Academy of Management Review, Vol. 23, No. 3 (Jul., 1998), pp. 567-588